Density graded polyethylene foams: Effect of processing conditions on mechanical properties. Issue 1 (January 2019) - Cusson, E; Akbarzadeh, AH; Therriault, D; Rodrigue, D
Uniform foams (UF) and density graded foams (DGF) were produced by using similar or different temperatures on both sides of a compression molding system. The samples were produced using linear low density polyethylene as the matrix and activated azodicarbonamide as the chemical blowing agent. Morphological properties of the produced samples were analyzed via scanning electron microscopy to relate them to their mechanical properties. In particular, flexural and impact properties are reported for samples produced under a range of temperatures (140–200°C) and blowing agent concentration (0.7–1.0 wt%). The experimental results showed that a significant difference can be obtained in flexural modulus (up to 17%) and impact strength (up to 48%) depending on the side the stress is applied on. In all cases, the DGF showed better mechanical responses than UF of similar relative density for the range of conditions tested.